2021
DOI: 10.3390/biom11050697
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and Stem Cells—Two to Tango for Tissue Repair?

Abstract: Macrophages (MCs) are present in all tissues, not only supporting homeostasis, but also playing an important role in organogenesis, post-injury regeneration, and diseases. They are a heterogeneous cell population due to their origin, tissue specificity, and polarization in response to aggression factors, depending on environmental cues. Thus, as pro-inflammatory M1 phagocytic MCs, they contribute to tissue damage and even fibrosis, but the anti-inflammatory M2 phenotype participates in repairing processes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 222 publications
0
18
0
Order By: Relevance
“…Tissue repair is a complex mechanism that takes place over four phases: inflammatory process, cell proliferation, differentiation, and ECM remodeling. The process involves cytokines, growth factors, and MMPs [15]. Despite a large literature on CGF use and applications in the regenerative medicine field [21,23], up to the present, no data are provided on the metabolomic profile of CGF, and very few studies investigated the kinetic release of CGF growth factors and MMPs over a long time and analyzed the CGF cellular component.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue repair is a complex mechanism that takes place over four phases: inflammatory process, cell proliferation, differentiation, and ECM remodeling. The process involves cytokines, growth factors, and MMPs [15]. Despite a large literature on CGF use and applications in the regenerative medicine field [21,23], up to the present, no data are provided on the metabolomic profile of CGF, and very few studies investigated the kinetic release of CGF growth factors and MMPs over a long time and analyzed the CGF cellular component.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the resident and circulating cells in the processes of tissue regeneration is well established [14,15]; therefore, besides growth factors and molecules contained in and released by CGF, we focused on the characterization of its cellular components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue repair is a complex mechanism that takes place through inflammatory processes, cell proliferation, differentiation, and matrix remodeling. Several mediators can be involved including cytokines, growth factors, and matrix-degrading enzymes [ 31 ]. Despite the large literature on CGF use and applications in the regenerative medicine field [ 30 , 32 ], up to the present, few data are provided on the effects of CGF in improving the bioactivity of the dental implant surface as well as osseointegration processes and tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…BM-MSCs have been reported to regulate macrophage phenotype in the context several disorders [ 35 37 ]. Recently, using a murine model of diabetic wound healing, Zhang et al demonstrated that BM-MSCs induced the functional restoration of vascular endothelial cells by polarizing macrophages into an anti-inflammatory phenotype [ 38 ].…”
Section: Discussionmentioning
confidence: 99%